A Variable sampling interval EWMA Xbar chart for the mean with auxiliary information - Ng, P. S.; Khoo, B. C.; Yeong, W. C. *; Lim, S. L. (Springer, 2020)
It is a well-known fact that the exponentially weighted moving average (EWMA) type control chart is very effective in detecting small and moderate shifts. To further enhance the sensitivity of the EWMA control chart in shift detection, this paper proposes the variable sampling interval EWMA chart by using a single auxiliary variable (AI) (abbreviated as VSI EWMA-AI) to monitor the process mean, where the statistic of the proposed chart is based on the information of the study and auxiliary variables. The performance of the proposed chart is evaluated by using the average time to signal (ATS) criterion, where the derivation of ATS formula is presented in this paper. Subsequently, the performance of the proposed chart is compared with the existing EWMA-AI chart in literature. The comparison shows that the VSI EWMA-AI chart has better detection ability in mean shifts than the EWMA-AI chart.